B1, b2 are the lengths of each base. h is the height (height) Remember that the bases are the two parallel sides of the trapezoid. The height (or height) of a trapezoid is the perpendicular distance between its two bases.
The two parallel sides of a trapezoid are the base. If we call the long side b1 and the short side b2, then the base of the parallelogram is b1 + b2.
A = 1 / 2h (b1 + b2) Multiply both sides by 2. 2A = h (b1 + b2) Multiply both sides by 1 / h. 2A / t = b1 + b2.
Definition: The sum of two vectors A = (A1, A2 , An) and B = (B1, B2 , Bn) is defined by. A + B = (A1 + B1, A2 + B2 , An + Bn) Note: adding vectors is only defined if both vectors have the same size. Example: (2, 3) + (0, 1) = (2 + 0.3 + 1) = (2, 2).
A trapezoid is a four-sided figure with two parallel sides. For example, in the diagram on the right, the bases are parallel. To find the area of a trapezoid, take the sum of the bases, multiply the sum by the height of the trapezoid, and divide the result by 2. The formula for the area of a trapezoid is: o.
The area of this parallelogram is the height (half the height of the trapezoidal shape) multiplied by the base (the sum of the bases of the trapezoidal shape), so the area is half the height x (base1 + base2). Since the parallelogram is made up of exactly the same things as the trapezoid, so is the area of the trapezoid.
(A² + B²) = (A + B) ² 2AB. E (A²B²) = (AB) ² + 2AB.
a2 b2 = (a + b) (a - b).
a2 + b2 = (b + 2) 2
An integer is an integer that can be greater than 0 (indicated as positive) or less than 0 (indicated as negative). Zero is neither positive nor negative. Two integers equidistant from the origin in opposite directions are said to be opposite.
If α and are the two roots of the equation ax2 + bx + c, then α + β = (b / a) and α × β = (c / a). Solution:
Square means to multiply an expression by itself: (ab) 2 means (ab) (ab). And if you rearrange and rearrange, you will see that there are two aces and two bbs, all multiplied by a2b2.
a - b) 2 = a2 - 2ab + b2 a2 + b2 = (a - b) 2 + 2ab. 3. (a + b + c) 2 = a2 + b2 + c2 + 2 (ab + bc + ca)